Psychosocial Factors Associated With Increased Adolescent Non-suicidal Self-Injury During the COVID-19 Pandemic - Du, Na; Ouyang, Yingjie; Xiao, Yu; Li, Yunge (Frontiers in Psychiatry, 2021)
Non-suicidal self-injury (NSSI) in adolescents hospitalized with psychiatric disorders continues to increase after the outbreak of COVID-19. This study aimed to explore the relationship between the pandemic and NSSI among adolescents and whether the composition of psychosocial factors related to NSSI has changed during the pandemic. Through the retrospective analysis of medical records retrieved from the electronic system of the psychiatric hospital located in Chengdu from January 2016 to March 2021, 609 medical records of adolescents were obtained. The main potential psychosocial factors were determined by deductive content analysis. Among the 609 adolescents, 420 subjects had engaged in NSSI, while 189 did not. We found that the percentage of adolescents who had engaged in NSSI in 2016 was only 29.2%, reaching 34.5% in 2017, 45.7% in 2018, 61.3% in 2019, 92.5% in 2020, and 95.9% in 2021. In the binary logistic regression model, female sex (OR = 0.073, 95% CI: 0.028–0.186), older age (OR = 1.234, 95% CI: 1.030–1.478), having a single parent (OR = 7.865, 95% CI: 3.997–15.476), having experienced trauma (OR = 2.192, 95% CI: 1.032–4.654), having experienced social isolation from peers (OR = 8.139, 95% CI: 4.037–16.408), having experienced body-focused bullying (OR = 3.078, 95% CI: 1.295–7.318), overuse of a mobile phone in the parents' opinions (OR = 4.354, 95% CI: 1.380–13.738), having attempted suicide (OR = 9.120, 95% CI: 4.492–18.512), and during the pandemic (time point is January 30, 2020) (OR = 5.399, 95% CI: 1.679–17.357) were the factors that were significantly associated with NSSI. When comparing the differences in psychosocial factors between the pre-pandemic and the during-pandemic groups, the results showed that the family constitution, parent–child relationships, mobile phone overuse, and stressful learning were important factors. Tailored interventions geared towards changed psychosocial factors should be formulated.